2000
DOI: 10.1063/1.1290010
|View full text |Cite
|
Sign up to set email alerts
|

C–H⋯O H-bonded complexes: How does basis set superposition error change their potential-energy surfaces?

Abstract: Geometries, vibrational frequencies, and interaction energies of the CNH¯O 3 and HCCH¯O 3 complexes are calculated in a counterpoise-corrected ͑CP-corrected͒ potential-energy surface ͑PES͒ that corrects for the basis set superposition error ͑BSSE͒. Ab initio calculations are performed at the Hartree-Fock ͑HF͒ and second-order Mo "ller-Plesset ͑MP2͒ levels, using the 6-31G(d,p) and D95ϩϩ(d, p) basis sets. Interaction energies are presented including corrections for zero-point vibrational energy ͑ZPVE͒ and therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 18 publications
2
30
0
Order By: Relevance
“…Because the complex uses a basis set larger than the one used by monomers, in most cases this error models the complex to be too attractive. As it has been studied before, when BSSE is corrected along the whole surface, important changes in the potential energy surface appear, not only in the energy but also in the position of the minimum as well as its topology [19,20]. In this article the counterpoise correction (CP) proposed by Boys and Bernardi [21] is used to correct the potential energy surface's BSSE, geometry and frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Because the complex uses a basis set larger than the one used by monomers, in most cases this error models the complex to be too attractive. As it has been studied before, when BSSE is corrected along the whole surface, important changes in the potential energy surface appear, not only in the energy but also in the position of the minimum as well as its topology [19,20]. In this article the counterpoise correction (CP) proposed by Boys and Bernardi [21] is used to correct the potential energy surface's BSSE, geometry and frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we have chosen a series of well-known chemical processes for which the use of a too much rigid basis set or a too simple method of calculation leads to wrong PESs. [33][34][35][36][37][38][39] The results obtained will reveal that the hardness profile can be used as a good indicator of the presence of spurious stationary points on the calculated PES.…”
Section: ͑1͒mentioning
confidence: 99%
“…At the HF and MP2 levels, the equilibrium geometry of HCCH¯O 3 has C 2v symmetry with the 6-31G(d,p) basis set, whereas with the D95ϩϩG basis set it has a lower C s symmetry. Salvador et al 39 evidenced some years later that the spurious C 2v equilibrium geometry obtained with the 6-31G(d,p) basis set was due to the BSSE. Thus, these authors found that when the BSSE is corrected during the geometry optimization process, both the 6-31G(d,p) and D95ϩϩG basis sets predict the same C s equilibrium geometry.…”
Section: Hcch¯omentioning
confidence: 99%
See 2 more Smart Citations